Charge Ordering in K4Fe3F12 from a First Principles Study. Issue 2 (13th January 2017) - Liu, Shanshan; Xu, Yuanhui; Qu, Nianrui; Zhang, Yizhi; Wang, Jing; Sun, Keju; Hao, Xianfeng
Abstract: First‐principles calculations based on the generalized gradient approximation plus the on‐site Coulomb repulsion (GGA+U) approach, as implemented in the VASP code, have been used to investigate the structural, electronic as well as magnetic properties of a new charge‐ordered iron fluoride material, K4 (Fe 2+ )(Fe 3+ )2 F12, within a layered perovskite‐related structure. Our results established that K4 Fe3 F12 is a Mott‐Hubbard insulator, and adopts a magnetically ground state where the Fe 2+ and Fe 3+ spins are arranged in an approximately antiparallel manner to each other, in agreement with the experimental observations. Although the total 3d charge disproportion is rather small, an order parameter, defined as the difference between the dz 2 orbital occupations of the the Fe 3+ and Fe 2+ cations, provides explicit evidence on the charge ordering. Strong hybridization between F 2 p and Fe 3 d states leads into the nearly complete loss of the separation between the total charges at the Fe 2+ and Fe 3+ cations. Furthermore, the unique occupation of the dz 2 orbital is responsible for the stability of the antiferromagnetic spin ordering and the charge ordering pattern. Abstract : K4 Fe3 F12 is charge ordering, although the total charge disproportion and derivation of the magnetic moments is rather small, due to the strong screening effect of F 2 p ‐ Fe 3 d covalent bonds. More interesting, our results indicated that the on‐site Coulomb repulsion Hubbard U is essential to determine the electronic structure and charge ordering scenario, while magnetic configurations is not as well as the spin‐orbit coupling.